Production cross sections of short-lived silver radionuclides from Pd-nat(p,xn) nuclear processes - Khandaker, Mayeen Uddin; Kim, G.; Kim, K. (Elsevier, 2012)
Production cross-sections of short-lived Ag-103, Ag-104m andi Ag-104g radionuclides from proton-induced reactions on natural palladium (Pd) were measured up to 41 MeV by using a stacked-foil activation technique combined with high resolution gamma-ray spectrometry. The present results are compared with the available literature values as well as theoretical data calculated by the TALYS and the ALICE-1PPE computer codes. Note that production cross-sections of the Ag-104m radionuclide from Pd-nat(p,xn) processes has been measured here for the first time. Physical thick target yields for the investigated radionuclides were deduced from the respective threshold energy to 41 MeV taking into account that the total energy is absorbed in the targets. Measured data of the short-lived Ag-103 radionuclide are noteworthy due to its possible applications as a precursor for the indirect production of widely used therapeutic Pd-103 radionuclide via Pd-nat(p,xn)Ag-103 -> Pd-103 processes. On the other hand, the investigated Ag-104 radionuclide finds importance due to its potential use as a diagnostic and positron emission tomography (PET) imaging analogue. Above all, measured data will enrich the literature database leading to various applications in science and technology. (C) 2011 Elsevier B.V. All rights reserved.